Formalization and formulation of problems of modeling the movement of heterogeneous flows of people - Komyak, Valentina (PHYSICO-MATHEMATICAL MODELLING AND INFORMATIONAL TECHNOLOGIES, 2023)
Studies show that there is a relationship between the flow density and the category of traffic comfort. In this paper, methods for modeling the movement of people depending on the category of comfort are proposed. It is shown that a change in the comfort category of the flow of people can be taken into account in the method of individual flow movement both by changing the spatial shape of objects and by setting different minimum and maximum allowable distances between them. An integral part of these tasks is to take into account the conditions for not crossing objects and the conditions for their inclusion in the ways and means of evacuation. Analytical expressions of the conditions of non-intersection of objects of new spatial forms and the conditions of their placement in regions, taking into account the distances between them, were obtained using normalized quasi-phi-functions, on the basis of which were built new models of the movement of heterogeneous flows of people.